Functional requirements analysis-based method for product platform design in axiomatic design - Cheng, X. (Journal of Digital Information Management, 2012)
Today's companies are increasingly being challenged to develop platform-based product families to increase variety of products, while keeping production costs low. In order to provide effective platform-based method and systematically analyzing the customer needs on product design, the functional requirements are classified into basic functional requirements, expectable functional requirements and adjunctive functional requirements. Axiomatic design theory was applied to zigzagging mapping between functional requirements and design parameters, and a new decomposition method to link design matrix and design structure matrix was proposed based on the functional requirements. The common parameters were determined through analyzing the sensitivity of functional requirements to design parameters and the relation degree among design parameters. By way of illustration, a family of drum brake was designed and its results demonstrated the effectiveness and practical value of the method.
Keywords: Axiomatic design; Functional requirements analysis; Product platform; Relation degree